Equity market informational efficiency: history and development - Qaiser Munir; Sook, Ching Kok (2017)
In economics and finance, the term ‘efficiency’ has several distinct connotations. This term can be used to refer to allocation efficiency, informational efficiency, operational efficiency or technical efficiency.1 At the outset, it is necessary to clarify that in this chapter ‘efficiency’ only refers to informational efficiency, such that prices are based on the best available information (Howell and Bain, 2005: 540). According to Latham (1986), the most common implicit definition for informational efficiency is that prices will not change if all private information is publicized. Zou (2011) interprets this type of efficiency as the effectiveness of market information.